The Influence of Safety Behavior, Motivation and Work Discipline on Employee Performance of PT Dahana Job Site Project PT Antang Gunung Meratus - Muhammad Aminuddin; Sulastini Sulastini; Maskur Maskur (Green Publisher Indonesia, 2024)
The competition in the era of globalization, which is marked by the formation of the industrial revolution 4.0, has an impact on increasing business competition and sustainable development is very much needed for companies to survive. The research method used in the research is the Quantitative Method with a Correlational Statistical Technique approach. The results of this research are the regression coefficient for the Safety Behavior variable (X1) with a value of 0.376 which means that Safety Behavior has a positive and significant effect on employee performance, every additional unit of the Safety Behavior variable (X1) will increase PT Dahana Job's Employee Performance (Y). The regression coefficient for the motivation variable (X2) with a value of 0.380 means that motivation has a positive and significant effect on employee performance. The Motivation variable (X2) will increase Employee Performance (Y) at PT Dahana Job Site Project PT Antang Gunung Meratus. The regression coefficient for the Work Discipline variable (X3) with a value of 0.352 means that work discipline has a positive and significant effect on employee performance. The variables Safety Behavior (X1), Motivation (X2) and Work Discipline (X3) simultaneously have a positive and significant effect on employee performance at PT Dahana Job Site Project PT Antang Gunung Meratus by 77.7%. This means that 77.7% of the dependent variable of employee performance can be explained by the independent variables of safety behavior, motivation and work discipline